2010
DOI: 10.2514/1.j050338
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Analogy Formulations Accelerated by Fast Multipole Method for Two-Dimensional Aeroacoustic Problems

Abstract: The calculation of acoustic field solutions due to aeroacoustic sources is performed for a large number of observer locations. Sound generation by vortex shedding is computed by a hybrid method and an accurate two-dimensional direct calculation, and the results are compared. The hybrid approach uses direct calculation for near-field source computations and the Ffowcs-Williams-Hawkings equation as the acoustic analogy formulation. The integrations of surface dipole and volume quadrupole source terms appearing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…However, recent studies have shown that at moderate Mach numbers, quadrupole sources can have a non-negligible effect on far-field acoustic predictions [3,4]. Additionally, it has been demonstrated that quadrupole sources have a significant impact on far-field predictions involving airframe configurations, particularly those with wake interactions [5,6].…”
Section: Doi: 102514/1j053713mentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent studies have shown that at moderate Mach numbers, quadrupole sources can have a non-negligible effect on far-field acoustic predictions [3,4]. Additionally, it has been demonstrated that quadrupole sources have a significant impact on far-field predictions involving airframe configurations, particularly those with wake interactions [5,6].…”
Section: Doi: 102514/1j053713mentioning
confidence: 99%
“…The investigation of the noise sources for airfoil and cylinder vortex shedding frequencies is presented using a hybrid methodology which employs DNS for near field source computations and the FW-H equation as the acoustic analogy formulation. The integrations of surface dipole and volume quadrupole source terms appearing in the FW-H formulation are accelerated by a fast multipole method [5] that incorporates convective effects. Furthermore, with the present numerical formulation, it is possible to investigate the individual contributions of the quadrupole sources and separate the surface dipole sources from the airfoil and from the cylinder.…”
Section: Doi: 102514/1j053713mentioning
confidence: 99%
“…The integrations of these volumetric sources are computed along a subset region of the flowfield including the wake plus turbulent boundary layer regions, where the magnitude of non-linear sources is non-negligible. The surface and volume integrations of dipole and quadrupole source terms are performed using a 3D convective wideband multi-level adaptive FMM [10,11,12] to reduce the computational cost of the calculation of aeroacoustic integrals in the FWH formulation. The developed numerical capability allows the analysis of each noise source individually as well as the effects of convection on the computation of noise radiated by these sources.…”
Section: Flow Simulations and Acoustic Predictionsmentioning
confidence: 99%
“…The acoustic predictions are performed by the FWH acoustic analogy formulation [9] and incorporate convective effects. The surface and volume integrations of dipole and quadrupole source terms appearing in the FWH equation are performed using the 3D convective wideband multi-level adaptive fast multipole method (FMM) developed in [10,11,12] to reduce the computational cost of the calculation of aeroacoustic integrals in the FWH formulation. With the method applied in this work the computational cost of evaluating the aeroacoustic integrals is considerably reduced.…”
Section: Introductionmentioning
confidence: 99%
“…The numerical tool has been previously validated for several simulations of compressible flows involving sound generation and propagation. 3,4,7 …”
Section: Flow Simulationsmentioning
confidence: 99%